2009
DOI: 10.1002/hec.1448
|View full text |Cite
|
Sign up to set email alerts
|

A game of two halves? Incentive incompatibility, starting point bias and the bidding game contingent valuation method

Abstract: The bidding game (BG) method of contingent valuation is one way to increase the precision of willingness to pay (WTP) estimates relative to the single dichotomous choice approach. However, there is evidence that the method may lead to incentive incompatible responses and be associated with starting point bias. While previous studies in health using BGs test for starting point bias, none have also investigated incentive incompatibility. Using a sample of respondents resident in Burkina Faso, West Africa, this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 22 publications
1
27
0
5
Order By: Relevance
“…It has been shown to generate more efficient estimates than those based on a single question (Hanemann, Loomis & Kanninen, 1991), or based on an open-ended follow-up question (Haab & McConnell, 2002;Watson & Ryan, 2007). Moreover, such an approach is suggested in contexts where prices are variable (McNamee, Ternent, Gbangou, & Newlands, 2010), as is the case with MHOs.…”
Section: Theoretical Frameworkmentioning
confidence: 93%
“…It has been shown to generate more efficient estimates than those based on a single question (Hanemann, Loomis & Kanninen, 1991), or based on an open-ended follow-up question (Haab & McConnell, 2002;Watson & Ryan, 2007). Moreover, such an approach is suggested in contexts where prices are variable (McNamee, Ternent, Gbangou, & Newlands, 2010), as is the case with MHOs.…”
Section: Theoretical Frameworkmentioning
confidence: 93%
“…There is a literature on contingent valuation and willingness to pay in health economics, where it has been shown that iterative tasks may be susceptible to biases because respondents do not interpret the series of binary choices as independent. [73][74][75] In effect, the binary choice versions of TTO and LT-TTO can be interpreted as iterative (LT-)TTO surveys, but ones in which the individual tasks are presented at random order.…”
Section: Binary Choice Methodsmentioning
confidence: 99%
“…out of pocket or insurance premium in CV; or TTO or SG in heatlh state valuation), or routing and ordering (double bounded dichotomous choice or bidding game in CV; ping pong or titration in TTO), framing effects or other sources of bias. These other issues have alreadyreceived extensive attention in health economics, in particular in the CV literature (Smith, 2003;Hackl and Pruckner, 2005;McNamee, 2010;Luchini and Watson, 2013;Ternent and Tsuchiya, 2013).…”
Section: Summary and Discussionmentioning
confidence: 99%